Estudo de glicídios de Angiostrongylus cantonensis e o papel no imunodiagnóstico - Veríssimo, Carolina De Marco (2015)
Angiostrongylus cantonensis is a nematode parasite, main etiologic agent of the eosinophilic meningitis (EM) in humans, a disease endemic in many tropical and sub tropical countries. The diagnosis of EM involves clinical evaluation, eosinophils counting >10% in liquor, and consuming historical of raw mollusks, as they are the intermediate hosts of the Angiostrongylus. Definitive diagnosis through larvae visualization in the liquor is rare. Serological test, mainly involving the 31-kDa component detection, which presents high sensitivity and specificity, has been employed as an alternative way for diagnostic. The 31-kDa antigen is composed for glycoproteins and tentatives in producing it in a recombinant way, using either prokaryotic or eukaryotic models, were inable to mantain immunological recognition, probably due the lack or deficient glycosilation of the molecules. Due the lack of information about A. cantonensis glycans and the need of producing a standard antigen able to be used worldwide in a diagnostic test, the main goal of this work was to study the A. cantonensis glycan profile and their role on the immune diagnosis of EM. It was used total soluble extract (TE) and excretory-secretory products (ES) as sources of glycans and glycoconjugates. The N-linked glycans and glycoconjugates from A. cantonensis female TE and 31-kDa antigen were analyzed and identified by mass spectrometry (MS) and lectin array, and the immunogenecity of these molecules were characterized by dot blot and Western blots. Furthermore, It was investigated the biosynthesis routes of glycans using in silico analysis of the Angiostrongylus genome and transcriptome dataset. N-glycans containing complex structures, with truncated antennas containing terminal with galactose and N-acetylgalactosamine, and core α1-6 fucosylated were identified. Lectin array analysis could also dentify Gal and GalNAc structures in Angiostrongylus glycoconjugates. Eight genes involved with biosynthesis of N-glycans, among them GCS1; GANAB, MAN1, MGAT2 and FUT8; and three involved with O-glycan biosynthesis, GALNT, C1GALT1 e OFUT1 were found by in silico analysis. Immunogenicity of the 31-kDa antigen is tottaly dependent of N-glycans and not to O-glycans. Modeling of proteins of the 31kDa component showed N-glycosilation sites and predicted structures that were the same identified by MS analysis. Taking together, the data generated in this study shown the glycan importance for angiostrongyliasis diagnosis and also the glycan repertoire that Angiostrongylus produces. This work is an important contribution to the development of a standard diagnosis for EM and also for new perspectives in the study of angiostrongyliasis diagnosis, parasite biology and host-parasite relationship.